Draft Annual Plan 1986-87 Volume : XI Hill Areas Government of Assam - Planning Commission (Planning Commission, 1986)
The annual plan allocation for 1985-86 is Rs. 149.00 lakhs and the amount of allocation is expected to be utilised fully. The seventh plan proposals have been formulated keeping in view of Strengthening and consolidation of activities already takenup and also for establishment of new health institutions with a view to achieve the goal of "Health for all by 2000 A.D."
Government of Assam